Multistage financing of technical start-up companies in silicon valley - Dean, Burton V.; Giglierano, Joseph J. (Journal of Business Venturing, 1990)
Financing remains an issue that entrepreneurs face long after their initial financing has been obtained. In technical companies, that face changing customers, competitors, and technology, the need to finance new products to replace earlier products can be of vital importance to growth and survival. Venture capital firms that invest in technical companies also recognize the need for subsequent financing to maintain growth and thus protect the initial investment. This research explored both the venture capitalist's and the entrepreneur's viewpoints. The principal questions asked in the research were (1) How are subsequent rounds of investment considered and made by venture capitalists? and (2) What problems occur in the entrepreneur's search for subsequent funding? A combination of in-depth interviews and mailed questionnaires was used in the research to obtain responses from a sample of venture capitalists and entrepreneurs in Silicon Valley. This approach produced observations on the venture capitalists' methods of making risk-return trade-offs and on the reasons why entrepreneurs face problems in obtaining funding for second, new products. Specifically, it was found that venture capital firms reduce the risk associated with funding young companies by showing preferences for certain stages of financing, or for funding single-versus multiple-round investments. These preferences appear to be idiosyncratic, and entrepreneurs must be careful to deal with venture capitalists whose tendencies are consistent with the entrepreneurs' goals. It was also found that a major problem faced by entrepreneurs seeking funding for second products is the effort required for the search. This effort takes away from their ability to perform day-to-day management activities at a crucial time in the growth of the firm. Implications are drawn for improving the effectiveness of entrepreneurs' and venture capitalists' efforts, as well as for future research.